Dexmedetomidine provides optimum conditions during awake fiberoptic intubation in simulated cervical spine injury patients - Pooja Chopra; Madhu Bala Dixit; Aashish Dang; Vibhuti Gupta (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: We undertook this study to assess if a small-dose of dexmedetomidine (DEX) for conscious sedation during awake fiberoptic intubation (AFOI) in simulated cervical spine injury (CSI) patients provides optimum conditions and fulfills the need of postintubation neurological examination required in such patients. The aim was to assess the efficacy of DEX on arousability and patient's comfort during AFOI in simulated CSI patients. Material and Methods: In this prospective, randomized double-blind study, 100 American Society of Anesthesiologists Grade I-II patients aged between 18 and 65 years scheduled for elective surgery under general anesthesia underwent AFOI under conscious sedation with DEX. After locally anesthetizing the airway and applying a cervical collar, patients either received DEX 1 μg/kg over 10 min followed by 0.7 μg/kg/h maintenance infusion or normal saline in the same dose and rate during AFOI. Targeted sedation (Ramsay sedation score [RSS] ≥2) during AFOI was maintained with midazolam [MDZ] in both groups. Statistical Analysis was performed using unpaired Student's t-test, Chi-square test, Mann-Whitney test and Wilcoxon-w test. Results: The total number of patients requiring MDZ and the mean dose of MDZ required to achieve targeted sedation (RSS ≥2) was significantly less in DEX group compared to the placebo group (P < 0.001 ). Similarly, patient satisfaction score, heart rate, systolic, diastolic and mean arterial pressure and respiratory parameters were significantly better in DEX group (P < 0.001). Postintubation arousability in the two groups was comparable (P = 0.29). Conclusions: Dexmedetomidine provides optimum sedation without compromising airway or hemodynamic instability with better patient tolerance and satisfaction for AFOI. It also preserves patient arousability for the postintubation neurological assessment.